PENGARUH ASUPAN ENERGI DAN PROTEIN, POLA ASUH, DAN STATUS KESEHATAN TERHADAP KEJADIAN STUNTING PADA ANAK USIA 12-36 BULAN DI PUSKESMAS TILANGO KECAMATAN TILANGO KABUPATEN GORONTALO - Anasiru, M. Anas; Domili, Indra (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2018)
ABSTRACT Stunting occurs to 170 million children aged under 5 years with prevalence of 40% in South Asia and 50% in Sub-Saharan Africa. Finding of Basic Health Research in Indonesia in 2010 shows that there are 35.6% of stunting babies and it improves to 37.2% in 2013. Then, data of Department of Health in Gorontalo District in 2013 show that number of stunting babies at Puskesmas (Public Health Center) of Tilango remains in the highest level. Objective this research aims to identify and add insight about influence of energy and protein intake, parenting and health status over stunting incident at babies aged 12 to 36 months. This research is conducted in Puskesmas of Tilango area, District of Gorontalo. Research hypothesis is H1: there is influence of energy and protein intake, parenting and health status on stunting incident at babies aged 12 to 36 months, H0: there is no influence of energy and protein intake, parenting and health status on stunting incident at babies aged 12 to 36 months. Methodology: it applies analytical observational study with case control design in which the case group is stunting babies while control group is non-stunting babies. Finding p value of energy intake is 0,010 with value of OR for 1,664, protein intake is 0,000 with value of OR for 2,172, parenting is 0,000 with value of OR for 4,714 and status of health is 0,096. Conclusion: There is influence of energy and protein intake as well as parenting on stunting incident at babies aged 12 to 36 months at Puskesmas of Tilango, Sub-district of Tilango, District of Gorontalo. There is no influence of health status on stunting incident at babies aged 12 to 36 months at Puskesmas of Tilango, Sub-district of Tilango, District of Gorontalo. Keywords: Stunting, Protein, Parenting ABSTRAK Stunting terjadi sekitar 170 juta pada anak usia dibawah 5 tahun dengan prevalensi 40% di Asia Selatan dan 50% di sub Sahara Afrika. Hasil Riset Kesehatan Dasar di Indonesia tahun 2013 masih terdapat 37.2% balita stunting meningkat dari 35,6% tahun 2010. Puskesmas Tilango terdapat balita stunting tertinggi di Kabupaten Gorontalo. Tujuan penelitian ini mengidentifikasi dan menambah wawasan tentang pengaruh asupan energi dan protein, pola asuh dan status kesehatan terhadap kejadian stunting pada anak umur 12-36 bulan. Kegiatan penelitian ini dilaksanakan di wilayah Puskesmas Tilango Kecamatan Tilango Kabupaten Gorontalo. Hipotesis penelitian ini H1: Ada pengaruh asupan energi dan protein, Pola Asuh, dan status Kesehatan terhadap kejadian stunting pada anak usia 12-36 bulan, H0: Tidak ada pengaruh asupan energi dan protein, Pola Asuh, dan status Kesehatan terhadap kejadian stunting pada anak usia 12-36 bulan. Metodologi yang digunakan yaitu studi observational analitik dengan rancangan case control dimana sebagai kelompok kasus adalah balita stunting dan kelompok kontrol yaitu balita non stunting. Hasil Nilai p Asupan energi 0,010 nilai OR 1,664, Asupan protein 0,000 nilai OR 2,172, Pola asuh 0,000 nilai OR 4,714, dan status kesehatan 0,096. Kesimpulan Ada pengaruh asupan energi, Protein dan pola asuh terhadap kejadian stunting Anak usia 12-36 bulan di Puskesmas Tilango Kecamatan Tilango Kabupaten Gorontalo. Tidak ada pengaruh status kesehatan terhadap kejadian stunting Anak usia 12-36 bulan di Puskesmas Tilango Kecamatan Tilango Kabupaten Gorontalo. Kata Kunci: Stunting, Protein, Pola Asuh